UPAYA PENGASUHAN SANTRI DALAM MENINGKATKAN LIFE SKILL MELALUI EXPERIENTIAL LEARNING DI PONDOK PESANTREN MINHAJUL MUNA NGRAYUN PONOROGO - Anisa Yahyani, Wien; Ayok Ariyanto; Sigit Dwi Laksana; Riyanto; Watik Widianingrum (LPPM STAI Muhammadiyah Probolinggo, 2023)
The purpose of this study is: (1) to know and describe the efforts of student care in improving student life skills; and (2) the implementation of experiential learning in activities carried out by student care in improving life skills; (3) to know and describe the impact of the implementation of the Experiential Learning method in improving life skills. This study is a study that uses a descriptive qualitative approach with observation, interview and documentation methods. In this case, the researcher will describe how the efforts of student care in improving student life skills through the Experiential Learning method. This study found several findings, namely: (1) Efforts of student care in improving life skills are a) providing thematic training, b) holding regular workshops (2) Activities formed by student care to improve student life skills through the Experiential Learning method are a) assignments to become Imam and Khatib for male students, b) assignments to become imams of Yasinan and Tahlil in the surrounding community for female students; (3) The impact of the Experiential Learning method in improving life skills a) improving the ability to communicate well, b) improving expertise in a particular field.